Evaluation of antimicrobial effectiveness of pimaricin-loaded thermosensitive nanohydrogel coating on Arzúa-Ulloa DOP cheeses - Fuciños, C. (2017)
Supplementary data related to this article can be found at http://dx.doi.org/10.1016/j.foodcont.2016.10.028.